Boosting the electrochemical performance of lithium titanate at sub-zero temperature with Mo, S doping, and addition of MXene. (December 2022) - Pu, Z.; Li, H.; Yang, Z.; Zhang, Y.; Liu, Y.; Dong, G.; Li, Y.
Abstract: It is critical to exploit anode materials with high safety and excellent electrochemical performance at sub-zero temperature for lithium-ion batteries. Although Li4 Ti5 O12 (LTO) is safe compared to graphite anode, its poor electrochemical performance at low temperature is a big challenge to be overcome. In this report, lithium titanate nanosheets with large surface area are prepared and their electrochemical performance is boosted by the combination of multiple heteroatoms doping and introduction of MXene. Electrochemical experiments show that the Mo, S co-doped sample nanocomposites display high reversible specific capacity, good rate capability, and cycling lives at the temperature of −20 °C, showing the great capability of Mo, S co-doping heteroatoms to improve the performance of LTO at sub-zero temperature. Density functional theory (DFT) calculation indicates that the Mo, S co-doping can introduce impurity energy level to promote the electronic conductivity of LTO, in favor of promoting the electrochemical performance. Graphical abstract: Scheme Schematic synthesis of Mo, S-LTO/Mx. Image 1 Highlights: Ultrathin Mo, S-LTO/Mx nanocomposites with high specific surface area are prepared. The Mo, S co-doping plays a key role in enhancing the performance of LTO at low temperature. The introduced MXene nanosheets further enhance the charge transfer of LTO. The as prepared nanocomposites deliver 106 mAh/g at 5 A/g and −20 °C in LIBs. Such nanocomposites show excellent cycle stability in a wide temperature.